2014
DOI: 10.1007/s00705-014-2299-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Australian-like dicot-infecting mastrevirus in Pakistan

Abstract: Although members of five distinct viral species in the genus Mastrevirus (family Geminiviridae) infect dicotyledonous plants in Australia, in the remainder of the world, only a single dicot-infecting mastrevirus, chickpea chlorotic dwarf virus (CpCDV) has ever been identified. This virus has been found infecting leguminous hosts in Africa, the Middle East and the Indian subcontinent. To further explore the diversity of CpCDV in Pakistan, ten full mastrevirus genome sequences from chickpea and lentil plants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…48 Additionally we identified four new strains (CpCDV-M, -N, -O and -P) and show that recombination 49 has played a significant role in the diversification of CpCDV, at least in this region. Accounting for 50 observed recombination events, we use the large amounts of data generated here to compare patterns (Kraberger et al, 2015). Whereas CpCDV has 86 been found in the Middle East (including Turkey), Africa and the 87 Indian subcontinent, CpYDV has so-far only been found in Pakistan.…”
mentioning
confidence: 99%
“…48 Additionally we identified four new strains (CpCDV-M, -N, -O and -P) and show that recombination 49 has played a significant role in the diversification of CpCDV, at least in this region. Accounting for 50 observed recombination events, we use the large amounts of data generated here to compare patterns (Kraberger et al, 2015). Whereas CpCDV has 86 been found in the Middle East (including Turkey), Africa and the 87 Indian subcontinent, CpYDV has so-far only been found in Pakistan.…”
mentioning
confidence: 99%
“…Despite the huge effect of CSD and their wide distribution, very few species has been identified like in Sudan and Pakistan [24], and another three identified in possibly new species Australia [41]. Also the CpCDV from Syria has been directly identified after these new species [33].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the mastrevirus species infect monocotyledonous hosts, while viruses belonging to seven mastrevirus species infect dicotyledonous hosts. Five of the dicot‐infecting mastreviruses have only been described in Australia: chickpea chlorosis virus (CpCV), chickpea chlorosis Australia virus (CpCAV), chickpea redleaf virus (CpRLV), chickpea yellows virus (CpYV) and tobacco yellow dwarf virus (TYDV) (Hadfield et al , ; Kraberger et al , , ; Kvarnheden et al , ). Chickpea yellow dwarf virus has been identified in Pakistan (Kraberger et al , ), while chickpea chlorotic dwarf virus (CpCDV) has been found in many regions including the Middle East (Iran, Oman, Yemen, Syria and Turkey), Africa (Morocco, Sudan, South Africa, Egypt, Tunisia, Nigeria and Burkina Faso) and the Indian subcontinent (India and Pakistan) (Kraberger et al , ; Kanakala & Kuria, ).…”
Section: Introductionmentioning
confidence: 99%